A method for backward calculation of debris in a post blast scene. (January 2018) - Verolme, E.K.; Van der Voort, M.M.; Smits, R.; Weerheijm, J.; Koh, Y.H.; Kang, K.W.
Abstract: There is limited knowledge on deriving the strength of an explosion based on the observed explosion effects. Existing methods are based primarily on the effects of blast overpressure on surrounding structures. Window breakage and structural damage are well studied and are widely used to derive most probable explosion strengths. Other explosive effects such as debris throw are usually left out of such forensic analyses. In this paper, a quantitative method is presented that can be used to obtain the explosion strength based on debris throw. When the method is applied together with analysis of other evidence at a post blast scene, more accurate predictions of the original amount of explosive can be obtained. An overview of the required information that has to be collected from a post-blast scene is outlined, which will aid in the backward calculations that will be carried out in the next stage. This calculation method is applied to two case studies, which illustrate that it is applicable to events involving both low and high order accidental explosion events. Besides accidents, the method is also applicable to intentional explosion scenarios such as terrorist attacks. It is shown that the added value of such a method to forensic investigation depends on the precision of the data collected. Therefore, it is recommended that first responders not only register the impact locations but also attempt to identify the part of the donor installation from which the debris originated. Furthermore, estimates should be made of the launch height and ballistic properties of the debris and information should be recorded on obstructions and terrain properties in the vicinity. In this way, the quality of the backward calculations can be optimized.